Analisis Pelaksanaan Pembiayaan Musyarakah Pada Bank Syariah ( Studi di Bank Syariah Indonesia KC. Kutacane ) - Sugianto Sugianto; Sriwahyuni Sriwahyuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The study was conducted at Bank Syariah Indonesia KC. Kutacane with the aim of understanding the execution of the musyarakah reform at Bank Syariah Indonesia KC. Kutacane and the compliance of the musyarakah reform practice with the DSN-MUI No.08/DSN-MUI/IV/2000 fatwa on musyarakah. This study employs a deskriptif kualitatif method using the technique of gathering data through open communication with the parties involved in the musyarakah reform at Bank Syariah Indonesia KC.Kutacane. The study’s findings indicate that the musyarakah redevelopment practice implemented by Bank Syariah Indonesia KC. Kutacane’s implementation of this practice complies with the DSN-MUI/IV/2000 fatwa regarding musyarakah in several poins. However, the fourth poin’s remuneration is explained as follows: a mitra may declare that if the profit exceeds a certain amount, kelebihan or prosentase will be given to the individual. In practice at BSM, profit has already been determined by taking into account the modalities.